Thinking through making : the rural building workshop - Neokorides, Peter Alexander (School of Architecture, Planning and Geomatics, 2016)
This thesis is about the link between thinking and making, and how designing and physically building or prototyping what is designed (or parts there of) aids in the generation of ideas, and has a potential for architectural education. The ideas that have transpired through the course of the year from building models and doing research for my theory and technology papers has led me in the direction of developing components and techniques for construction made from easily sourced tools and materials - ones from local industry and the landscape - that give rise to a tectonic expression as well as allows for an adaptable type of architecture. The methodology informing the design has therefore developed from the bottom up through the use of these components, as well as from the top down by means of a structural concept. The first part of the paper looks at the theory of making which deals with aspects of making in current society that I find relevant to this thesis. Part two and three of this paper is comprised of reciprocal components. Part two deals with the theory of structure and how my findings have helped guide the process of making, and have led to an appropriate structural system for my concept of a 'growing' or adaptable building. The third part of this paper describes the models I have built this year to illustrate the concept of 'techne', or the process of creation that is guided by the thing made, in order to demonstrate the qualities that materials possess, as well as how the act of making can be a design generator. It also describes how the initial stage of building models has led to the exploration of structural systems and components, and how models relating to the programme and site have been able to start informing the form of a building. The fourth and final part of this paper looks at the programme, site, and materiality of the 'Rural Building Workshop'.